PENYUSUNAN JADWAL PETUGAS SEKURITI DENGAN PROGRAM GOL - Marbun, Herlina; Lily, Endang; Gamal, M. D. H. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses a goal programming technique for security rostering. The goal programming used is the weighted or non-preemptive. This technique is implemented to solve a case study in a real life problem of security rostering in a construction company. The results of computation with LINGO show that security rostering by goal programming is better than manual rostering.